Violent Becomings State Formation, Sociality, and Power in Mozambique - Bertelsen, Bjørn Enge (Ethnography, Theory, Experiment, 2016)
Violent Becomings conceptualizes the Mozambican state not as the bureaucratically ordered polity of the nation-state, but as a continuously emergent and violently challenged mode of ordering. In doing so, this book addresses the question of why colonial and postcolonial state formation has involved violent articulations with so-called 'traditional' forms of sociality. The scope and dynamic nature of such violent becomings is explored through an array of contexts that include colonial regimes of forced labor and pacification, liberation war struggles and civil war, the social engineering of the post-independence state, and the popular appropriation of sovereign violence in riots and lynchings.